2019
DOI: 10.1007/s10533-019-00627-9
|View full text |Cite
|
Sign up to set email alerts
|

Soil nitrogen cycle unresponsive to decadal long climate change in a Tasmanian grassland

Abstract: Increases in atmospheric carbon dioxide (CO 2) and global air temperature affect all terrestrial ecosystems and often lead to enhanced ecosystem productivity, which in turn dampens the rise in atmospheric CO 2 by removing CO 2 from the atmosphere. As most terrestrial ecosystems are limited in their productivity by the availability of nitrogen (N), there is concern about the persistence of this terrestrial carbon sink, as these ecosystems might develop a progressive N limitation (PNL). An increase in the gross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Also, our results are in line with meta-analyses that observed that the effect of temperature on N cycling processes is less pronounced in grasslands, in comparison with other ecosystem types [ 36 , 73 ]. In addition, other studies in grassland systems also reported no significant effects of elevated temperature on nitrification [ 72 , 74 ]. Our results indicate that increased temperature might have altered abiotic and biotic soil parameters that may be masking individual temperature effects.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Also, our results are in line with meta-analyses that observed that the effect of temperature on N cycling processes is less pronounced in grasslands, in comparison with other ecosystem types [ 36 , 73 ]. In addition, other studies in grassland systems also reported no significant effects of elevated temperature on nitrification [ 72 , 74 ]. Our results indicate that increased temperature might have altered abiotic and biotic soil parameters that may be masking individual temperature effects.…”
Section: Discussionmentioning
confidence: 95%
“…Likewise, eCO 2 did not affect gross N mineralization and NH 4 + levels, highlighting that substrate availability for nitrifiers did not change in response to eCO 2 . In addition, other studies also reported very few effects of elevated atmospheric CO 2 concentration on belowground N processes in heathlands and temperate grasslands [ 70 72 ] showing that soil parameters such as pH and inorganic N concentrations likely play a more significant role than increased atmospheric CO 2 on overall nitrification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The weak or missing N cycle response under FACE treatment in some ecosystems -grassland, heathland or forest observed here and elsewhere (Wild et al 2018;Schleppi 2019;Rütting 2020), could be due to limitation of another nutrient, such as P (Dijkstra et al 2013;. At EucFACE, evidence derived from Eucalyptus leaf C:N:P stoichiometry revealed strong P re-translocation compared to N in both ambient and CO 2 treated trees (Crous et al 2019), emphasising that P is highly limiting for the trees in this ecosystem.…”
Section: Discussionmentioning
confidence: 46%
“…Using a 14 C approach, Farrell et al (2013) determined amino acid and peptide half-life (alanine, dialanine and trialanine) across grassland, bush and forest in Western Australia. With 15 N techniques, Rütting & Hovenden (2020) determined gross N mineralization rate in a Tasmanian grassland (TasFACE). Our study is however, the first conducted in Australian woodland within an eCO 2 field facility (EucFACE).…”
Section: Discussionmentioning
confidence: 99%